Soluble N-Acetylgalactosamine-Modified Antigens Enhance Hepatocyte-Dependent Antigen Cross-Presentation and Result in Antigen-Specific CD8+ T Cell Tolerance Development - Damo, Martina; Wilson, D. Scott; Watkins, Elyse A.; Hubbell, Jeffrey A. (Frontiers in Immunology, 2021)
Hepatocytes compose up to 80% of the total liver and have been indicated as important players in the induction of immunologic tolerance in this organ. We show that hepatocytes possess the molecular machinery required for the cross-presentation of extracellular antigens. Using a derivative of the model antigen ovalbumin (OVA) covalently modified with a polymer containing multiple N-acetylgalactosamine residues (pGal-OVA) that enhance extracellular antigen uptake by mimicking the glycome of apoptotic debris, we show efficient hepatocyte-dependent induction of cross-tolerance of both adoptively transferred OT-I cells and endogenous OVA-specific CD8+ T lymphocytes, for example inducing tolerance to OVA-expressing skin transplants. Our study confirms that hepatocytes are capable of inducing peripheral tolerogenesis and provides proof of concept that they may be a valuable candidate for in vivo targeted tolerogenic treatments.